Kerja Sama Guru PAI dengan Orang Tua dalam Membina Karakter Religius Peserta Didik di SDN 05 Padang Tarok Kecamatan Baso Kabupaten Agam - Annisa Sri Lestari; Inesri Inesri (Kampus Akademik Publiser, 2024)
Education plays an important role in shaping the intelligence and character of students. However, globalization and the lack of parental attention to children's character education often cause moral and religious problems among students. Therefore, cooperation between Islamic Education (PAI) teachers and parents is needed to foster the religious character of students. This study aims to determine the forms of cooperation between IRE teachers and parents as well as the factors that support and hinder its implementation at SD 05 Padang Tarok, Baso District, Agam Regency. This study uses a descriptive qualitative method with data collection techniques through observation and interviews with IRE teachers and parents. Data analysis was carried out through the stages of data reduction, data presentation, and verification. The results showed that the cooperation between PAI teachers and parents in fostering religious character was carried out through direct communication, correspondence, telephone communication, and the involvement of parents in school activities. However, the implementation of this cooperation still faces obstacles such as the busyness of parents, the large number of students, and the influence of the surrounding environment. In general, this cooperation has a positive impact on the formation of students' religious character, although consistency needs to be improved.